The effect of eight weeks'feedback training program on lower extremity kinematic and performance during jump landing tasks in the men with selected motor control defects. - Ashrafizadeh, Mohadeseh; Norasteh, Ali Asghar (Journal of Bodywork & Movement Therapies, 2025)
The present study aims to investigate whether eight weeks' feedback improves the range of motion in lower extremity joints(in the four phases of eccentric, concentric, maximum knee flexion, and landing moment) and performance in the individuals with motor control defects or not. The present research is a randomized clinical trial study before and after the intervention. Thirty-four male recreational athletes with movement control defects were selected based on the study criteria and then randomly assigned to a control group and an intervention group. Kinematic and performance data were recorded while the participants performed jump-landing movement tasks in two stages before and after the two-month jump training program. To analyze the data, the two-way analysis of variance and Bonferroni statistical tests were used for each movement task at the significance level of P < 0.05. There was a significant difference between the values of Reactive Strength Index (RSI) in the intervention and the control groups in drop vertical jumps and countermovement jumps (p = 0.001). The results of the present study indicated that two months' feedback improved the athletes' kinematic variables and jumping performance.